Epicardial Transplantation of Autologous Cardiac Micrografts During Coronary Artery Bypass Surgery - Nummi, Annu; Mulari, Severi; Stewart, Juhani A.; Kivistö, Sari; Teittinen, Kari; Nieminen, Tuomo; Lampinen, Milla; Pätilä, Tommi; Sintonen, Harri; Juvonen, Tatu; Kupari, Markku; Suojaranta, Raili; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: Cardio-regenerative cell therapies offer additional biologic support to coronary artery bypass surgery (CABG) and are aimed at functionally repairing the myocardium that suffers from or is damaged by ischemia. This non-randomized open-label study assessed the safety and feasibility of epicardial transplantation of atrial appendage micrografts (AAMs) in patients undergoing CABG surgery. Methods: Twelve consecutive patients destined for CABG surgery were included in the study. Six patients received AAMs during their operation and six patients were CABG-operated without AAMs transplantation. Data from 30 elective CABG patients was collected for a center- and time-matched control group. The AAMs were processed during the operation from a biopsy collected from the right atrial appendage. They were delivered epicardially onto the infarct scar site identified in preoperative late gadolinium enhancement cardiac magnetic resonance imaging (CMRI). The primary outcome measures at the 6-month follow-up were (i) patient safety in terms of hemodynamic and cardiac function over time and (ii) feasibility of therapy administration in a clinical setting. Secondary outcome measures were left ventricular wall thickness, change in myocardial scar tissue volume, changes in left ventricular ejection fraction, plasma concentrations of N-terminal pro-B-type natriuretic peptide levels, NYHA class, number of days in hospital and changes in the quality of life. Results: Epicardial transplantation of AAMs was safe and feasible to be performed during CABG surgery. CMRI demonstrated an increase in viable cardiac tissue at the infarct site in patients receiving AAMs treatment. Conclusions and Relevance: Transplantation of AAMs shows good clinical applicability as performed during cardiac surgery, shows initial therapeutic effect on the myocardium and has the potential to serve as a delivery platform for cardiac gene therapies. Trial Registration:ClinicalTrials.gov, identifier: NCT02672163.